Controlled synthesis of CeVO4 hierarchical hollow microspheres with tunable hollowness and their efficient photocatalytic activity. Issue 31 (18th July 2018) - Ding, Jinjin; Liu, Xuan; Wang, Miao; Liu, Quan; Sun, Tongming; Jiang, Guoqing; Tang, Yanfeng
Abstract : CeVO4 hierarchical hollow microspheres assembled from nanoscaled building units (nanoparticles, nanocubes and nanoflakes) were synthesized by a one-step hydrothermal approach usingl -Asp as the morphology-directing agent. Abstract : Well-dispersed hollow CeVO4 microspheres with tunable hollowness and porosity have been synthesized via a simple hydrothermal method usingl -aspartic acid (l -Asp) as the capping agent. The products were characterized by XRD, SEM, TEM and DRS. The XRD results showed that the as-prepared samples were tetragonal phase CeVO4 with high crystallinity. SEM and TEM observations indicated that the hierarchical hollow microspheres with different hollowness were constructed from nanoparticles, cubes or nanoflakes. N2 adsorption–desorption measurements revealed that the BET specific surface area of the typical CeVO4 hollow microspheres was up to 106.54 m 2 g −1 . During the synthesis, the amount ofl -Asp and the reaction time were found to play important roles in determining the growth process and final morphologies of the CeVO4 products. Time-dependent experiments clearly revealed that the CeVO4 hierarchical hollow microspheres were governed by the self-assembly and Ostwald ripening process. Rhodamine B (RhB) was used as the dye pollutant for evaluating the photocatalytic properties of the products under UV radiation. The CeVO4 hierarchical hollow microspheres exhibited excellent photocatalytic activity and good stability even after five repeated cycles of use, indicating that the CeVO4 hierarchical hollow microspheres can be good candidates for photocatalytic degradation of organic pollutants.